Implementasi Pendekatan Contextual Teaching dan Learning (CTL) dalam Pembelajaran Bahasa Indonesia di Lingkungan Siswa SMPN 4 Mangaarabombang - Jumriani Jumriani; Sudarsono Sudarsono (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
The purpose of this study is to describe the implementation of the Contextual Teaching and Learning (CTL) approach in Indonesian language instruction at SMPN 4 Mangarabombang and to analyze its effect on students’ motivation and learning outcomes. This research employed classroom action research (CAR) in two cycles involving 30 eighth grade students. Data collection was carried out through classroom observation checklists, motivation questionnaires, achievement tests, and semi structured interviews. The results indicate that applying CTL increased student engagement and improved classroom interaction through linking learning material to real student contexts, facilitating group discussion, presentation, inquiry, and reflection. Students’ motivation showed significant growth, from an average score of 60 before intervention to 82 after the second cycle. Learning outcomes also rose markedly: average pre test score was 55, post test cycle I was 68, and post test cycle II reached 80. The percentage of students achieving the minimum competency criteria (KKM) increased from 30% before intervention to about 90% after cycle II. The study concludes that the CTL approach is effective in enhancing both motivation and learning outcomes in Indonesian language instruction at SMPN 4 Mangarabombang. It is recommended that teachers continue to develop contextually relevant teaching materials, conduct regular reflection, and design collaborative learning structures so all students participate actively.